2016
DOI: 10.1519/ssc.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Laterality on Soccer Performance

Abstract: THE PURPOSE OF THIS ANALYSIS IS TO DETERMINE WHETHER THERE IS A LEFT FOOT ADVANTAGE IN SOCCER PERFORMANCE. THE OUTCOME OF THE REVIEWED ARTICLES SUGGESTS THAT THERE IS A LEFT FOOT ADVANTAGE IN SOCCER, NO MATTER HOW SMALL THAT MAY BE. NEVERTHELESS, THIS CONCLUSION MAY BE TENTATIVE BECAUSE LITTLE WORK WAS CONDUCTED IN THIS AREA AND THE FOCUS IS VERY DIVERSE. THE CURRENT REVIEW RAISES IMPORTANT QUESTIONS FOR FUTURE WORK. THE EXAMINATION OF THE TEMPORAL OCCLUSION PARADIGM AND THE COMPARISON OF SPATIAL ORIENTATIONS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Studies on laterality in football have focused mainly on field players rather than on goalkeepers (Petro & Szabo, 2016). Anyway, insight can be obtained for the case of the movement; the differential speed of the extremities in football players differ significantly (27.68 m.s -1 for the execution of the kick with the preferred leg vs. 23.49 for the non-preferred leg; Vaverka et al (2003), so rendering this disparity as a proxy of goalkeeper's performance when using his legs to dive to the side of their preferred leg or the other.…”
Section: Lateralitymentioning
confidence: 99%
“…Studies on laterality in football have focused mainly on field players rather than on goalkeepers (Petro & Szabo, 2016). Anyway, insight can be obtained for the case of the movement; the differential speed of the extremities in football players differ significantly (27.68 m.s -1 for the execution of the kick with the preferred leg vs. 23.49 for the non-preferred leg; Vaverka et al (2003), so rendering this disparity as a proxy of goalkeeper's performance when using his legs to dive to the side of their preferred leg or the other.…”
Section: Lateralitymentioning
confidence: 99%
“…Laterality in football is another relevant aspect to consider, as it can influence players' performances during the practice of this sport (Petro & Szabo, 2016). Laterality indicates the tendency to use one side of the body predominantly over the other, such as in the case of the dominant hand, foot, and eye.…”
Section: Introductionmentioning
confidence: 99%
“…Laterality is a multidimensional construct (Badzakova et al, 2010) referring to the preferential use of one side of the body compared to the other (Petro & Szabo, 2016; Sadeghi et al, 2000). Past motor research has shown that laterality related to cerebral hemispheric dominance for motor control, is also affected by both environmental and genetic factors (Musalek, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the ability of the non-dominant hemisphere to control the contralateral side of the body, the dominant cerebral hemisphere has a predominant influence on motor control, creating greater motor precision, speed and coordinated actions on that side (Teixeira et al, 2003). Moreover, while being right-handed and right-footed is most common, with only 10% of the general population left-handed (Papadatou-Pastou et al, 2008; Raymond & Pontier, 2004), the prevalence of being left-handed or left-footed is higher among athletes in various sports (e.g., handball, basketball, fencing, and boxing) (Harris, 2010; Petro & Szabo, 2016; Ziyagil et al, 2010). Cerebral hemispheric dominance is more closely related to lower extremity preference than other lateral dominance preferences, (Bryden, 1998).…”
Section: Introductionmentioning
confidence: 99%